Integrasi Deep Learning dan Nilai Multikultural dalam Pembelajaran IPS sebagai Upaya Transformasi Pendidikan Sosial - Fitriah Ramadhani; Alimin Alwi; Najamuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the integration of deep learning approaches and multicultural values in Social Studies (IPS) learning as an effort to transform social education. The research uses a qualitative approach with an exploratory descriptive design through a case study in educational units that implement technology-based and reflective learning. Data collection techniques are conducted through observation, interviews, and documentation with informant selection through purposive sampling. The data analysis technique in this study uses the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and drawing conclusions. Data validity is obtained through source triangulation and technique triangulation. The research results indicate that: the implementation of deep learning is able to increase students' active engagement and promote a deep understanding of social phenomena; the integration of multicultural values is effective in fostering attitudes of tolerance, empathy, and appreciation for diversity; and there is an improvement in students' critical thinking skills and more inclusive social attitudes. In addition, the synergy between deep learning and multicultural education contributes to the development of 21st-century competencies such as communication, collaboration, and global awareness. Future research is recommended to involve more schools with different characteristics and to combine quantitative and qualitative approaches in order to obtain more comprehensive results regarding the effectiveness of integrating deep learning and multicultural values in social studies learning